Exploratory analysis of traditional risk factors of ischemic heart disease (IHD) among predominantly Malay Malaysian women - Norafidah Abdul Rashid; Azmawati Mohammed Nawi; Shamsuddin Khadijah (BMC, 2019)
Abstract Background The risk factors of ischemic heart disease (IHD) specific for women are less well studied. However, knowing the risk factors of IHD for women will empower women themselves to be better informed and thus can help them in decision making concerning their health condition. The objective of this study is to explore the commonly studied risk factors of ischemic heart disease (IHD) among a group of Malaysian women. Methods A case control study was conducted among 142 newly diagnosed IHD women patients registered in government hospitals in Terengganu, Malaysia and their 1:1 frequency matched population controls. Data on sociodemographic and socioeconomic profile, co-morbidities, lifestyle factors related to physical activities, dietary fat intake, stress, passive smoking history, anthropometric measurements and biochemical markers were obtained. Results Middle aged women were recruited with women diagnosed with diabetes (aOR = 1.92, 95% CI: 1.11-3.31), having low HDL-C (aOR = 3.30, 95% CI: 1.28-8.27), those with positive family history of IHD (aOR = 1.92, 95% CI:1.13-3.26) and passive smokers (aOR = 2.99, 95% CI:1.81-4.94) were at higher odds of IHD. Conclusions The findings are useful for public health interventions and policy making focusing on specific women population.